Conceptual and Theoretical Foundations of Research on Social and Cultural Processes in the Environment of the Titular Nation of the Ukrainian SSR during the 1960s and 1970s - Kindrachuk, Nadia (Historia i Polityka, 2023)
The article considers the сonceptual and theoretical foundations of research on social and cultural processes in the environment of the titular nation of the Ukrainian SSR during the 1960s and 1970s. It is characterized by the semantic content of concepts of “titular nation” and “indigenous people” in the Ukrainian SSR, identified primarily with Ukrainians, who were united by a single language, faith, spirituality, national traditions, customs, culture, ethnic origin and ancient residence on the territory of Ukraine, the official name of which was determined by their nationality. The conceptual components of the research are interpretation of the following concepts of: “Ukrainian ethnos”, “Ukrainian ethnic territory” or “Ukrainian ethnic land”, “national majority”, “national minority”, “nation-state”, “nonconformism”, “counterculture”, “sixties”, “dissidence”, “Ukrainian diaspora”, etc. Research of the conceptual and theoretical foundations of the outlined topic makes it possible to resolve controversial issues which have not been adequately covered in historical science, also makes it possible to specify the process of national self-expression of Ukrainians through cultural space, and allows to get new assessments, judgments and conclusions.